The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1136/jech-2014-204801
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent and body weight-dependent associations between environmental PAHs exposure and insulin resistance: Korean urban elderly panel

Abstract: BackgroundThe prevalence of metabolic diseases rises rapidly with an ageing population. Recent studies suggest the potential involvement of environmental chemicals in insulin resistance (IR) that plays a core role in the development of metabolic diseases. Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous components of outdoor and indoor air pollution. The influence of PAHs on IR may differ depending on sex and weight.ObjectivesWe examined the association between exposure to environmental PAHs and IR in Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In most cultures, males tend to have higher exposure to outdoor air pollution because of longer travel distances and work in industries that might use coal or other solid fuels, whereas females are traditionally responsible for more indoor housework and domestic cooking (25). However, a prior study suggested that elderly women tend to be more vulnerable to air pollution, particularly overweight women, which could increase the risk of diabetes (26). With the increasing numbers of the aging population as well as the increasing trend of women working outside, the burden of type 2 diabetes mellitus attributable to PM 2.5 pollution for both genders should be paid better attention.…”
Section: Discussionmentioning
confidence: 99%
“…In most cultures, males tend to have higher exposure to outdoor air pollution because of longer travel distances and work in industries that might use coal or other solid fuels, whereas females are traditionally responsible for more indoor housework and domestic cooking (25). However, a prior study suggested that elderly women tend to be more vulnerable to air pollution, particularly overweight women, which could increase the risk of diabetes (26). With the increasing numbers of the aging population as well as the increasing trend of women working outside, the burden of type 2 diabetes mellitus attributable to PM 2.5 pollution for both genders should be paid better attention.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution (including NO2, particulate matter, and SO2) was associated with an increased risk of diabetes in women but not in men (Brook et al, 2008;Sohn and Oh, 2017), whereas NOX and O3 was associated with diabetes in both men and women, but the association was stronger in women (Renzi et al, 2018). Polycyclic aromatic hydrocarbons (PAHs) were associated with insulin resistance in women but not in men (Choi et al, 2015). Lastly, in vivo exposure to bisphenol (BPA), a non-persistent endocrine-disrupting contaminant, induced early onset of T1D in female NOD mice, whereas males had a delayed development of T1D (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This association may be gender-dependent, being more distinct among women than men. (28)(29)(30)(31). Although the biological mechanisms underlying this association are still unclear, animal studies have shown that high levels of air pollution may be equivalent to a high-fat diet in terms of its effects, involving immune activation, endoplasmic reticulum (ER) stress, oxidative stress and CNS inflammation (32,33).…”
Section: Introductionmentioning
confidence: 99%